Eutrophication management in surface waters using lanthanum modified bentonite: A review. (15th June 2016) - Copetti, Diego; Finsterle, Karin; Marziali, Laura; Stefani, Fabrizio; Tartari, Gianni; Douglas, Grant; Reitzel, Kasper; Spears, Bryan M.; Winfield, Ian J.; Crosa, Giuseppe; D'Haese, Patrick; Yasseri, Said; et al.
Abstract: This paper reviews the scientific knowledge on the use of a lanthanum modified bentonite (LMB) to manage eutrophication in surface water. The LMB has been applied in around 200 environments worldwide and it has undergone extensive testing at laboratory, mesocosm, and whole lake scales. The available data underline a high efficiency for phosphorus binding. This efficiency can be limited by the presence of humic substances and competing oxyanions. Lanthanum concentrations detected during a LMB application are generally below acute toxicological threshold of different organisms, except in low alkalinity waters. To date there are no indications for long-term negative effects on LMB treated ecosystems, but issues related to La accumulation, increase of suspended solids and drastic resources depletion still need to be explored, in particular for sediment dwelling organisms. Application of LMB in saline waters need a careful risk evaluation due to potential lanthanum release. Graphical abstract: Highlights: High phosphorus binding efficiency of the lanthanum modified bentonite. Efficiency is reduced by the presence of humic substances and competing oxyanions. Low eco-toxicological and human health risks. Long term investigation are suggested to verify the impact on the ecosystem.